Dampak Lingkungan dari Teknologi Pengolahan Sampah Menjadi Energi di Indonesia: Perspektif Life Cycle Assessment - Amelinda Dhiya Farhah; Mochammad Chaerul; Haryo Satriyo Tomo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The principle of reduce, reuse, recycle (3R) serves as the main reference in waste management, but further efforts are needed to handle non-recyclable materials. Based on the waste management hierarchy, the next step is energy recovery through waste-to-energy (WtE). WtE technology can generate renewable energy as a substitute for fossil fuels while reducing waste disposal in landfills. Various WtE technology options are available, depending on the heterogeneous characteristics of waste. According to the Ministry of Public Works and Housing, waste treatment technologies in Indonesia include physical, biological-chemical, and thermal processes. Although WtE offers benefits, its potential impacts must also be considered. This study reviews trends in Indonesia regarding the use of the life cycle assessment (LCA) method as a tool for evaluating different WtE technologies from an environmental perspective. The review covers the analyzed functional units, selection of impact categories, supporting software, and the application of sensitivity analysis and data uncertainty. The findings from LCA applications can assist policymakers in designing sustainable WtE management strategies.